PSYCHOMOTOR DEVELOPMENT, SOCIAL-EMOTIONAL FUNCTIONING, QUALITY OF THE RELATIONSHIP WITH THE CAREGIVER AND MENTAL HEALTH IN EARLY CHILDHOOD, UNDER SEVERE RISK - CARMEN COSTEA-BĂRLUŢIU (Studia Universitatis Babes-Bolyai, 2011)
ABSTRACT. Interpersonal relationships are essential in early childhood and adaptation to interpersonal stress constitutes one of the main adaptive tasks during this period. Sixty-eight infants and toddlers at severe risk were included in our study, in order to investigate the impact of the relationship with the primary caregiver on the child's psychomotor development and mental health. We found significant associations between mental health status and psychomotor development, relationship functioning and psychomotor delay, as well as between social-emotional functioning and severity of the child's developmental delay. Several implications for the clinical practice with infants and toddlers were derived.